2021
DOI: 10.3389/fonc.2021.592319
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Resistance to Immunotherapy in Head and Neck Cancer Using Radiation: A Review

Abstract: Radiation therapy remains at the center of head and neck cancer treatment. With improvements in treatment delivery, radiation therapy has become an affective ablative modality for head and neck cancers. Immune checkpoint inhibitors are now also playing a more active role both in the locally advanced and metastatic setting. With improved systemic options, local noninvasive modalities including radiation therapy are playing a critical role in overcoming resistance in head and neck cancer. The aim of this review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 94 publications
0
16
0
Order By: Relevance
“…Treatment possibilities include tumor resection (primary and/or secondary tumor), radical neck dissection, immunotherapy, radiotherapy, checkpoint inhibitors (mainly targeting the cytotoxic T-lymphocyte-associated protein 4 (CTLA-4)), programmed cell death protein 1 (PD-1), programmed death-ligand 1 (PD-L1), and chemotherapy [ 40 , 41 , 42 , 43 , 44 , 45 ]. Recently, it has been showing how, in locally advanced HNSCC, the CTCs and the circulating tumor microemboli (CTM) have a significant prognostic impact on the potential role as predictors of induction chemotherapy benefit [ 46 ].…”
Section: Head and Neck Cancer And Alcoholmentioning
confidence: 99%
“…Treatment possibilities include tumor resection (primary and/or secondary tumor), radical neck dissection, immunotherapy, radiotherapy, checkpoint inhibitors (mainly targeting the cytotoxic T-lymphocyte-associated protein 4 (CTLA-4)), programmed cell death protein 1 (PD-1), programmed death-ligand 1 (PD-L1), and chemotherapy [ 40 , 41 , 42 , 43 , 44 , 45 ]. Recently, it has been showing how, in locally advanced HNSCC, the CTCs and the circulating tumor microemboli (CTM) have a significant prognostic impact on the potential role as predictors of induction chemotherapy benefit [ 46 ].…”
Section: Head and Neck Cancer And Alcoholmentioning
confidence: 99%
“…Therapeutic neck dissection and/or elective nodal irradiation (ENI) are utilized to minimize local and regional recurrence. Despite an aggressive treatment regimen, approximately 50% of patients with high-risk disease recur locally, regionally, or distantly by 3-years 2 . With the advent of immunotherapies, there was hope that patients with HNSCC would benefit from immune checkpoint inhibitors, but results of recent trials have dampened that hope 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical and clinical trials have shown that patients with increased T cell infiltration at the time of treatment for HPV-unrelated HNSCC have improved outcomes in response to immune checkpoint therapy 9 , 10 . Combining immunotherapies with radiation therapy to increase immune cell infiltration into the tumor microenvironment (TME) may improve response rates 11 13 . Hypofractionated stereotactic body radiation therapy (SBRT) may improve anti-tumor immune function instead of blunting it 13 .…”
Section: Mainmentioning
confidence: 99%
“…Combining immunotherapies with radiation therapy to increase immune cell infiltration into the tumor microenvironment (TME) may improve response rates 11 13 . Hypofractionated stereotactic body radiation therapy (SBRT) may improve anti-tumor immune function instead of blunting it 13 . Dose-escalation studies have shown that hypofractionation is optimal for stimulating an anti-tumor immune response while minimizing an immune wound-healing phenotype 14 17 .…”
Section: Mainmentioning
confidence: 99%